Democracy and Multicultural Education in Indonesia: A Bibliometric Study to Build Awareness and Collaborative Action - Rahmawati, Siti; Tamami, Fauziyah Qurrota Ayun; Tamami, Sabrina Failasufa; Tamami, Mochammad Mumtaz Rais (Universitas Muhammadiyah Surakarta, 2024)
With the use of bibliometric analysis drawn from several articles indexed in the Scopus database, this study seeks to map the evolution and direction of research on democracy and multicultural education to increase awareness and encourage collaborative action. The data found in levels from 1995 to 2024 will be analyzed to identify pertinent gaps. After that, the data was examined using R / R-Studio, VOSViewer, and Microsoft Excel software to identify keywords and document citation boosters. 193 publications that meet the established criteria, subject, and function were discovered by the researcher. This study's findings indicate a yearly increase rate. The scientific field and the annual quantity of studies published were taken into consideration when analyzing the obtained papers. This bibliometric analysis was restricted to data from Scopus. This study's drawback is that it only uses data sets or metadata from publications that are indexed in Scopus. In addition to offering suggestions for further research, this study gives a concise summary of the literature that scholars studying democracy and multicultural education for awareness-raising and collaborative action review can access.